2021
DOI: 10.3390/jcm10163576
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Prevalence and Factors Related to Frailty in Community-Dwelling Older Adults: A Multinomial Logistic Analysis

Abstract: Frailty is an age-related clinical condition that typically involves a deterioration in the physiological capacity of various organ systems and heightens the patient’s susceptibility to stressors. For this reason, one of the main research goals currently being addressed is that of characterising the impact of frailty in different settings. The main aim of this study is to determine the prevalence of Fried’s frailty phenotype among community-dwelling older people and to analyse the factors associated with frail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
10

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 50 publications
2
10
0
10
Order By: Relevance
“…However, some evidence of a relationship with depression has also been observed, but this association appears to be weaker and is less commonly reported [45][46][47]. An association has also been reported between mental pathology and frailty [48,49]. It has been observed that persons with a psychopathology tend to be less physically active, to have a less active social life, and to consume a less healthy diet, and that any or all of these factors could be related to a loss of strength and muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…However, some evidence of a relationship with depression has also been observed, but this association appears to be weaker and is less commonly reported [45][46][47]. An association has also been reported between mental pathology and frailty [48,49]. It has been observed that persons with a psychopathology tend to be less physically active, to have a less active social life, and to consume a less healthy diet, and that any or all of these factors could be related to a loss of strength and muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…Although few reports have investigated the relationship between functional disability measured using the WHODAS 2.0 and frailty instruments, 12‐item WHODAS 2.0 scores moderately correlated with activities of daily living in outpatients and surgical patients (Fujiwara et al, 2021; Ida et al, 2017). Considering the association between frailty and activities of daily living, functional disability and frailty also seemed to be closely related (Blanco‐Reina et al, 2021; Fried et al, 2004). As a result, functional disability and CPSP may also influence each other (Fujiwara, Ida, Watanabe, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, that meta-analysis ( 19) found a frailty prevalence of 51.5% and 29.8% among nursing home residents aged in average 86 years-old and hospital patients aged in average 80 years, respectively. The high prevalence of frailty may be explained by the high prevalence of osteo-articular (8)(9)(10)(11) and musculoskeletal (20) conditions in thermal/spa populations, given the important associations of osteo-muscular conditions and frailty (14)(15)(16)21). However, we cannot exclude the possibility that our findings on frailty prevalence was partly influenced by the assessment tool used, which was composed of subjectively measured criteria/items focusing mostly on mobility-related aspects (eg, mobility difficulties, climbing stairs, walking briskly); mobility is often impaired in people with osteo-articular and musculoskeletal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in joint pain and function after balneotherapy may be mediated by its potential anti-inflammatory effects (12,13). Osteoarticular diseases, which are very prevalent in older patients receiving thermal/spa treatments, are often associated to frailty in old adulthood (14)(15)(16). However, to the best of our knowledge, no study has examined the prevalence of frailty in patients receiving thermal/spa therapy.…”
Section: Introductionmentioning
confidence: 99%